2013
DOI: 10.1002/jsfa.6187
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids profile of Serbian unifloral honeys

Abstract: The floral origin of honey could be successfully evaluated by its amino acids profile coupled with chemometric analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 20 publications
6
32
1
Order By: Relevance
“…In the previous study on amino acid profile of these honeys, it was reported that some specific characteristics related to amino acids as properties of floral origin of honey can indicate a higher degree of variability, though most of the honeys contained 20 amino acids (Kıvrak, 2015). The high level of proline content in the studied honeys is in good consistency with that in other European honeys (Cotte et al, 2004;Kečkeš et al, 2013;Rebane & Herodes, 2008).…”
Section: Physicochemical and Chemical Propertiessupporting
confidence: 69%
See 2 more Smart Citations
“…In the previous study on amino acid profile of these honeys, it was reported that some specific characteristics related to amino acids as properties of floral origin of honey can indicate a higher degree of variability, though most of the honeys contained 20 amino acids (Kıvrak, 2015). The high level of proline content in the studied honeys is in good consistency with that in other European honeys (Cotte et al, 2004;Kečkeš et al, 2013;Rebane & Herodes, 2008).…”
Section: Physicochemical and Chemical Propertiessupporting
confidence: 69%
“…Knowledge of the chemical characteristics of honey, as one of the respected health-promoting natural products, is of general interest in terms of their protection against adulteration (Arvanitoyannis et al, 2005). A major concern of food control is to ensure that honey is authentic in respect of the legislative requirements of the standards of the Codex Alimentarius (Food and Agriculture Drganization, 2001;Kečkeš et al, 2013).…”
Section: Characterization Of Turkish Honeys Regarding Of Physicochemimentioning
confidence: 99%
See 1 more Smart Citation
“…), buckwheat ( Fagopyrum esculentum Moench .) and basil ( Ocimum basilicum L.) honeys, up to 258.1, 270.4 and 502.6 mg/kg, respectively. Kojic acid was identified and previously it was found in Manuka honey .…”
Section: Resultsmentioning
confidence: 99%
“…The possibility to distinguish honeys according to their botanical origin was tested by the analysis of a free amino acid profile of 192 samples of seven unifloral types of Serbian honey: acacia, lime, sunflower, rape, basil, giant goldenrod, and buckwheat, from six different regions (67). For that purpose, 17 amino acids were quantified by reversed-phase high-performance liquid chromatography with fluorescence detection.…”
Section: Authenticity Of Serbian Honeymentioning
confidence: 99%